2011
DOI: 10.1037/a0021686
|View full text |Cite
|
Sign up to set email alerts
|

Semantic categorical flexibility and aging: Effect of semantic relations on maintenance and switching.

Abstract: The authors studied the effects of aging on the flexible use of categorization rules based on thematic and taxonomic relations. Two components of flexibility were distinguished: maintenance of a categorical relation, and switching between two relations. Results showed that age affects these two components. In older adults, an effect of the nature of the categorical relations to be used was revealed. Older adults demonstrated a specific difficulty in the flexible use of taxonomic relations. Moreover, all adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 42 publications
3
24
0
4
Order By: Relevance
“…In a study of the development of conceptual representation and semantic categorical flexibility in children (Maintenant & Blaye, 2008), we found that a semantic relation can be used flexibly at precisely the same age as this relation is conceptualized. Previous studies on categorization (Annett, 1959; Cicirelli, 1976; Denney & Lennon, 1972; Lin & Murphy, 2001; Pennequin et al ., 2006; Smiley & Brown, 1979) and our previous results (Maintenant et al ., 2011) suggest an asymmetry of access to the representation of taxonomic and thematic relations in contrast to the more symmetrical access to the shape, colour, or number relations involved in the WCST. We could thus suppose that in addition to executive control (or set shifting ; Ridderinkhof et al .…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…In a study of the development of conceptual representation and semantic categorical flexibility in children (Maintenant & Blaye, 2008), we found that a semantic relation can be used flexibly at precisely the same age as this relation is conceptualized. Previous studies on categorization (Annett, 1959; Cicirelli, 1976; Denney & Lennon, 1972; Lin & Murphy, 2001; Pennequin et al ., 2006; Smiley & Brown, 1979) and our previous results (Maintenant et al ., 2011) suggest an asymmetry of access to the representation of taxonomic and thematic relations in contrast to the more symmetrical access to the shape, colour, or number relations involved in the WCST. We could thus suppose that in addition to executive control (or set shifting ; Ridderinkhof et al .…”
Section: Introductionsupporting
confidence: 85%
“…We also carried out several conceptual and executive measures. To investigate more precisely the importance of semantic relations in categorical flexibility, two versions of our categorical flexibility task were administered, one semantic (Maintenant et al ., 2011) and one perceptual (identical to the semantic task apart from the stimuli and rules used).…”
Section: Introductionmentioning
confidence: 99%
“…Older adults were tested because we sought to evaluate whether the complementary semantic systems suggested by the Schwartz et al (2011) study of adults with aphasia would hold for neurologically intact adults of a similar age. Older adults may rely on thematic knowledge more strongly than younger adults (Maintenant et al, 2011; Smiley & Brown, 1979), so age was included as a variable in our analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Rather, they have complementary features that are related to the complementary roles the objects play in events or scenarios. Thematic relations play an important role in children’s semantic representations (e.g., Nguyen & Murphy, 2003; Waxman & Namy, 1997) and continue to do so into adulthood (e.g., Lin & Murphy, 2001; Murphy, 2001; Ross & Murphy, 1999; see also Goldwater, Markman, & Stilwell, 2011; and for a review, see Estes et al, 2011), and may be even stronger for older adults (e.g., Maintenant, Blaye, & Paour, 2011; Smiley & Brown, 1979). …”
mentioning
confidence: 99%
“…Algunos autores han interpretado este cambio como el resultado de un proceso de declive cognitivo que impediría percibir y establecer adecuadamente relaciones taxonómicas (Annett, 1959;Cicirelli, 1976;Denney & Lennon, 1972). En un estudio reciente realizado por Maintenant, Blaye & Paour (2011) se encontró que para las personas mayores son más salientes las relaciones temáticas, de modo que es más difícil inhibirlas cuando así lo requiere la tarea. Otros autores consideran que las diferencias encontradas se corresponden con cambios comportamentales relacionados con percepciones ambientales diferentes pero igualmente adaptativas (Pennequin et al, 2006).…”
Section: Clasificaciónunclassified